Why Do Students Learn so Little? : Seeking Answers Inside Haiti's Classrooms - Adelman, Melissa; Baron, Juan D.; Blimpo, Moussa; Evans, David K.; Simbou, Atabanam; Yarrow, Noah (World Bank, Washington, DC, 2015)
The Haitian education system made substantial improvements in access over the last decade, such that today the majority of Haiti’s children are in school. Despite improvements, the primary education system is highly inefficient: children start primary school 2 years late on average, and fewer than 60 percent will reach the last grade of the cycle. At each school, classroom observations were conducted using the Stallings Classroom Snapshot instrument, and questions about the school calendar and daily schedule asked. The results provide a representative picture of class time and teacher classroom practice in the Nord and Nord Est departments, and while not representative of Haiti as a whole, do provide a starting point for better understanding the major constraint to achieving a high-quality education for all children: the quality of teacher instruction. Section two describes the sample of schools and the stallings instrument; sections three and four present the main results of the classroom observations on teacher time use and pedagogical practices; section five provides estimates of overall class time that students receive; and section six concludes.